Demandas populares nas outras visualidades e materialidades do transporte público de Curitiba: 1991-2011 - Caviquiolo, Suelen Christine (2017)
The present work investigates the visualities and materialities related to the popular demands in Curitiba’s public transport between 1991 and 2011. The design of a transport network articulated to the urban planning in 1960’s and 1970’s and the production and advertising of artifacts connected to the idea of “future” and “ecological city”, stimulated narratives that aimed to legitimize the success of Curitiba’s public transport. In a historical review of this transport, we indicate that the materialities and visualities of the and the Tube Stations and the Expresso, Ligeirinho and Ligeirão routes and vehicles were shaped and guided by the values and intentions of some groups involved and interested in urban transport planning and management. However, the deep analysis of everyday uses and visual and material productions that deal with the popular transport demands showed that this narrowed design of the transport network to attending private and corporate interests was manifested in the daily life as immobility. From images and documents produced to support the popular demands, in the local press and through the legislative petitions of the Câmara Municipal, it was possible not only to realize the possible mobilities but also to verify the production of more democratic and inclusive models to achieve the right to the city by redesigning Curitiba’s public transport.